The effects of interaction of Dopaminergic and Kisspeptin neural pathways on Ghrelin secretion in rats - Sadeghzadeh, Azizeh; Bayrami, Abolfazl; Mahmoudi, Fariba; Khazali, Homayoun; Asadi, Asadollah (Archives of Advances in Biosciences, 2018)
Dopamine, kisspeptin and ghrelin are important factors for regulating the reproduction and food intake. Finding the effective central or peripheral factors on ghrelin secretion attracted the attention of most researches. In the present experimental study, the effects of dopamine, kisspeptin and the GPR54 receptor signaling pathway role in the mediating the dopamine effects was determined on ghrelin secretion. Forty Wistar male rats weighing 220-250g in 8 groups received saline, 1nmol kisspeptin, 5, 15 or 45 microgram dopamine hydrochloride, simultaneous injections of 1nmol peptide 234 and kisspeptin, 15microgram dopamine and kisspeptin or peptide234 and 15microgram dopamine via third cerebral ventricle respectively. Blood samples were collected via tail vein. Mean serum ghrelin concentrations were determined by rat ghrelin kit and ELISA method. Kisspeptin significantly decreased mean serum concentration compared to saline group, while 15 or 45 microgram dopamine significantly increased mean serum ghrelin level compared to saline group. Kisspeptin significantly blocked the stimulatory effects of dopamine on ghrelin secretion compared to dopamine group. Dopaminergic and kisspeptin/GPR54 signaling pathways may interact to control the ghrelin secretion at hypothalamic level. Stimulatory effects of dopamine on ghrelin secretions could exert partly via decreasing the activity of hypothalamic kisspeptin neurons.